Extended Screening for Cystic Fibrosis-related Liver Disease Including Elastography in Children and Adolescents. Issue 5 (November 2020) - Højte, Christine; Jørgensen, Marianne Hørby; Jensen, Flemming; Katzenstein, Terese L.; Skov, Marianne
ABSTRACT: Objectives: Advances in treatment of cystic fibrosis (CF) have increased survival and thereby prevalence of patients with liver disease, making chronic liver disease one of the major complications of CF. We describe the prevalence of liver fibrosis, portal hypertension, and liver decompensation by extended screening for cystic fibrosis-related liver disease (CFLD) including ultrasound, elastography, and an extended panel of biochemical markers. Methods: A cross sectional study of CFLD in all pediatric CF patients (1–18 years) from the Copenhagen CF Center. Screening for liver disease included physical examination, biochemical analysis, Vibration-Controlled Transient Elastography (FibroScan), conventional ultrasound, and Real-Time Shear Wave elastography (SWE). Patients were scored according to Williams ultrasound scoring scale (WUSS) within 6 months. Results: A total of 84 consecutive patients (male sex 46.4%, median age 10.4 years) were included. Eight patients (9.5%) had both ≥2 abnormal results of sonographic methods and ≥2 abnormal biochemical results and were in this study categorized as having manifest CFLD. Manifest CFLD patients were significantly older and had a higher mean value of APRI, but no differences in gender, z -height, z -weight, z -BMI, FEV1%, or mean value of bilirubin or albumin were found. Conclusions: In total, 8 patients (9.5%) in this pediatric CF population were categorized as having CFLD according to both biochemical and sonographic tests. Consistency was found among the results of FibroScan and SWE. We suggest WUSS and either FibroScan or SWE, combined with GGT as diagnostic markers for CFLD.